(untitled) (Italian Journal of Public Health, 2011)
Background: Skin cancers, especially melanoma, are steadily increasing in incidence, and primary and secondary prevention measures have been proven to be useful in reducing skin cancer mortality. Aim: to promote a screening campaign among healthcare professionals of an Italian University/Hospital in order to detect not only an earlier recognition of potentially dangerous skin lesions, but also to verify if secondary prevention is useful, well-accepted and easy to perform among potentially more alerted people working in a healthcare background. Methods: The screening campaign was advertised through the Intranet of the Hospital. The screening took place once a week and a mean of 5-6 patients/week were examined. Every patient underwent a full-body skin examination integrated by handheld dermoscope at the Outpatient Clinic, Section of Dermatology, University/ Hospital of San Martino. In the case of clinically or dermoscopically suspicious lesions, an excision and histopathological examination were prescribed. Results: 138 patients (100 females and 38 males) were evaluated in the course of 1 year. 11 lesions were referred for excision and, among these, 1 was a melanoma in situ and 1 an atypical fibroxantoma. Conclusions: The rate of participation in the screening was low. However 2% of the screened patients presented a malignant lesion. We discuss the low adherence to the screening programme and suggest improving some aspects of communication, but we think that this kind of screening is useful because it can involve a good percentage of people who can undergo a check-up very easily in their own workplace.